"I'm stronger than I thought": Native women reconnecting to body, health, and place. (July 2016) - Schultz, Katie; Walters, Karina L.; Beltran, Ramona; Stroud, Sandy; Johnson-Jennings, Michelle
Abstract: This community-based research applied principles of wilderness experience programming and Indigenous knowledges in an exploratory intervention designed to address health disparities in a tribal community. Drawing on historical trauma frameworks, tribal members rewalked the Trail of Tears to consider its effect on contemporary tribal health. Qualitative data from tribal members suggest that engagement with place and experiential learning, particularly the physical and emotional challenge of the Trail, facilitated changes in health beliefs, attitudes, and behaviors. Deep engagement outside of traditional health service settings should be considered in interventions and may be particularly effective in promoting positive health behaviors in Native communities.